Dynamic plastid and mitochondrial genomes in Chaetopeltidales (Chlorophyceae) and characterization of a new chlorophyte taxon. Issue 6 (9th June 2022) - Robison, Tanner; Nelson, Jessica M.; Hauser, Duncan A.; Lewis, Louise A.; Li, Fay‐Wei
Abstract: Premise: Chaetopeltidales is a poorly characterized order in the Chlorophyceae, with only two plastid and no mitochondrial genomes published. Here we describe a new taxon in Chaetopeltidales, Gormaniella terricola gen. et sp. nov. and characterize both of its organellar genomes. Methods: Gormaniella terricola was inadvertently isolated from a surface‐sterilized hornwort thallus. Light microscopy was used to characterize its vegetative morphology. Organellar genomes were assembled, annotated, and analyzed using a variety of software packages. Results: The mitochondrial genome (66, 927 bp) represents the first complete mitochondrial genome published for Chaetopeltidales. The chloroplast genome, measuring 428, 981 bp, is one of the largest plastid genomes published to date and shares this large size and an incredible number of short, dispersed repeats with the other sequenced chloroplast genomes in Chaetopeltidales. Despite these shared features, the chloroplast genomes of Chaetopeltidales appear to be highly rearranged when compared to one another, with numerous inversions, translocations, and duplications, suggesting a particularly dynamic chloroplast genome. Both the chloroplast and mitochondrial genomes of G. terricola contain a number of mobile group I and group II introns, which appear to have invaded separately. Three of the introns within the mitochondrial genome encode homing endonucleases that are phylogenetically nested within those found in fungi, rather than algae, suggesting a possible case of horizontal gene transfer. Conclusions: These results help to shed light on a poorly understood group of algae and their unusual organellar genomes, raising additional questions about the unique patterns of genome evolution within Chaetopeltidales.